Development of Adobe Flash CS6 Based Learning Media on Student Learning Outcomes on Elasticity and Hooke's Law Material in High School - Bokori, Nur A S; Uloli, Ritin; Payu, Citron S.; Ntobuo, Nova E.; Setiawan, Dewa Gede Eka; Supartin, Supartin (Kasuari: Physics Education Journal (KPEJ), 2024)
The aim of this research is to evaluate the level of practicality of using Adobe Flash CS6-based learning media on elasticity and Hooke's law. This development research uses the ADDIE model to collect data about practicality. Learning implementation sheets, questionnaires for testing the practicality of learning media by teachers in individual tests, and student response test questionnaires in field tests are used to evaluate practicality. This study was conducted at SMA N 1 Kabila, which is located in Bone Bolango Regency. The research results show that learning media based on Adobe Flash CS6 on elasticity and Hooke's law is used very effectively during the learning process. With the average learning implementation for three meetings of 95.83%, the average teacher response of 82.61%, and the average response of students of 79.63% in the good category, it can be concluded that Adobe Flash-based learning media CS6 on elasticity and Hooke's law is used very effectively during the learning process.